Ecotourism Stakeholders Analysis in Bodogol Resort, Gunung Gede Pangrango National Park, West Java - Triprajawan, Tangguh; Soekmadi, Rinekso; Sunarminto, Tutut (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2024)
Tourist visits to Bodogol Resort, Gunung Gede Pangrango National Park (GGPNP), have experienced a downward trend from to 1998–2021. In addition, the Bodogol Resort is directly adjacent to the Lido Special Economic Zone (SEZ) with its main activity of tourism. The level of interest and influence of stakeholders involved in ecotourism development at Bodogol Resort and their role determine progress in ecotourism development. This study aims to assess the stakeholders and their role in ecotourism development at Bodogol Resort. Data collection was performed through observations, interviews, and document deepening. The analyses were performed both quantitatively and qualitatively. Stakeholder analysis was carried out to identify stakeholders, classify and map stakeholders, and analyze the relationships between stakeholders. Sixteen stakeholders related to ecotourism development in the Bodogol Resort were identified. The stakeholder mapping results are three key players, five subjects, and eight crowds. This shows that the stakeholders involved have not played as optimal roles as they should, the division of roles of who does what. Bodogol Resort is one of the key players with the highest level of influence and interest. The results of thematrix analysis of the relationships between stakeholders show that communication, coordination, and cooperation are low.